(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Adolescence is a critical period of growth which includes reproductive maturation and developmental transition. They are not only the future workforce but also the bearers of the next generation. If they are not properly fed then the country will not only able to reap the gain of demographic dividend but also suffer from vicious cycle of malnourishment. The Comprehensive National Nutrition Survey (CNNS, 2016-18) reveals that 28% of Indian adolescents are anaemic. West Bengal has the highest proportion of anaemic adolescents (45.6%) in the country. Materials and Methods: Unit level data from the CNNS was used to find out the factors of anaemia among adolescents in West Bengal. Observations were interpreted as per the WHO criteria. The data was analysed by stata version 16. Results: Findings shows that 46.5% of adolescents were suffering from anaemia, higher proportion of girls (65.3%) were anaemic compared to boys (25.6%). Girls were 5.7 times more likely to be anaemic compared boys (Adjusted Odds Ratio (AOR): 5.70, 95% CI = 4.04-8.04, p-value = 0.000). Other determinants were wealth quintile and knowledge of hand wash. Conclusion: Findings showed a sex and poverty are two important factors of anaemia among adolescents in West Bengal. Therefore, it requires a well thought poverty reduction and gender equality action to improve the anaemia status among the target group. Investing in adolescents not only ensures that they are healthy today, but that they grow into healthy adults in the future, who will in turn have families of good health.